Design and fabrication of flexible mesoporous Si-doped Al2O3 ultrafine fibers by electro-blow spinning (EBS) technique. Issue 13 (September 2017) - Zhou, Xing-hai; Ju, Jing-ge; Li, Zhen-huan; Zhang, Ma-liang; Deng, Nan-ping; Cheng, Bo-wen; Kang, Wei-min
Abstract: In this paper, flexible mesoporous Si-doped Al2 O3 ultrafine fibers were successfully prepared by electro-blow spinning (EBS) technology followed by a calcination process. The effects of spinning parameters, including air pressure, voltage, and solution injection rate on the morphology and diameter of fibers were investigated. The results showed that the spinning parameters played a key role on determining the morphology and diameter of fibers, and the specific surface area of fibers significantly increased with the increasing content of pore forming agents (polytetrafluoroethylene, PTFE), at the same time the pore size distribution was mainly concentrated at 5 nm. Most importantly, Si(OC2 H5 )4 was introduced to act as the flexible regulator which could inhibit the growth of alumina crystal, decrease the crystal size, and thus the flexibility of obtained mesoporous Si-doped Al2 O3 ultrafine fibers can be improved. Moreover, the fibers productivity by EBS method was higher than that of traditional electro-spinning. In the future, the mesoporous Si-doped Al2 O3 ultrafine fibers may perform desired function and spread their applications in different areas.